Determination of isotopic distribution of lead by a matrix assisted laser desorption/ionization versus a laser desorption/ionization time of flight mass spectrometry - Kamčeva, Tina T.; Nešić, Maja D.; Stoiljković, Milovan M.; Popović, Iva A.; Miletić, Jadranka N.; Rajčić, Boris M.; Petković, Marijana Ž.; Veličković, Suzana R. (HEMIJSKA INDUSTRIJA (Chemical Industry), 2017)
In this work it has been shown that both the laser desorption/ionization mass spectrometry (LDI MS) and the matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI TOF MS) are the simple and quick methods for determination of relative natural isotopic distribution of lead. The analysis of metal salts with these approaches does not require any time-consuming preparation of samples: a single run can take only a minute, and numerous information can be obtained. Results obtained in this work show that chosen matrix has no negative effect on quantitative determination of lead isotopes and support once more the applicability of MALDI TOF MS for lead isotope distribution determination in the sample and accurate data are obtained. Additionally, the generation of PbnOn and PbnOn–1 (n: 2–6) clusters have been successfully achieved in the positive mode, using the both LDI and MALDI methods. All stoichiometries were confirmed using isotopic pattern modelling.